Implementation of Discussion Method in Improving Learning Outcomes in the Subject of Aqidah Akhlak at MTs Miftahul Khoirot Cilamaya - Yusuf; Yulidar; Ningsih, Yusma; Yusri; Zahrah (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to analyze the implementation of the discussion method in improving learning outcomes of the material on the behavior of people who practice Asma'ul Husna of students at MTs Miftahul Khoirot Cilamaya Kulon, Karawang. The discussion method was chosen because it can encourage students to be more active in critical thinking, communicating, and understanding the values ​​of Asma'ul Husna in more depth through interactions between students. This study uses a quantitative approach with a quasi-experimental research design. The research sample consisted of grade VIII students who were divided into two groups, namely the experimental group using the discussion method and the control group using the lecture method. The results of the study showed that the application of the discussion method had a positive effect on improving students' understanding of the material being taught. Learning outcome data showed a significant difference between the experimental group and the control group, where the experimental group experienced a better increase in understanding. Thus, the discussion method has proven effective in improving student learning outcomes, especially in understanding and applying the values ​​of Asma'ul Husna in everyday life. These findings indicate that the discussion method can be used as an alternative learning strategy that is more interactive and can increase student involvement in the learning process.